Ameliorating Effects of Bioactive Peptides Extracted from Litopenaeus vannamei Wastes on Oxidative Stress, Glucose Regulation, and Autophagy Gene Expression in Nonalcoholic Fatty Liver-Induced Rats. (25th August 2022) - Moradian, Roya; Najdegerami, Ebrahim H.; Nikoo, Mehdi; Nejati, Vahid
Abstract : This study aimed to investigate the effect of bioactive peptides from Litopenaeus vannamei on oxidative stress, glucose regulation, and autophagy gene expression in the induced nonalcoholic fatty liver rats. Bioactive peptides used in the current study were extracted in a progressive rise in temperature (40–60°C) (GP). For this purpose, twenty-four healthy male rats (initial weight, 230.1 ± 22 g) were divided in four experimental groups including control (standard diet), HFD (high-fat diet), HFD + GP20, and 300 (high-fat diet + 20, 300 mg peptides/kg body weight). After 70 days, the results indicated that experimental treatments did not affect the body and liver weight (P > 0.05 ), although the higher liver weight was seen in HFD treatment. Based on these results, the use of GP peptides improved antioxidant enzymes and decreased MDA concentration, and a significant difference was observed between peptide treatments and HFD (P < 0.05 ). In comparison to the HFD group, significantly lower liver enzymes (ALT and AST) were seen in peptide treatments (P < 0.05 ). Also, the results indicated that the lowest amylase, alkaline phosphatase, glucose, insulin, HOMA-IR, and inflammation cytokines (TNF-ɑ and IL-6) were seen in peptide groups. The autophagy gene expression was measured in the liver cells, and the results showed that, unlike HFD treatment, the use of GP peptides decreased Beclin 1, Atg7, and P62 expression in male rat's livers. Overall, the results of the current study demonstrated that the use of GP peptides at low concentration shows significant hypoglycemia and antioxidant properties in nonalcoholic fatty liver-induced rats.